2020
DOI: 10.1097/bco.0000000000000872
|View full text |Cite
|
Sign up to set email alerts
|

Considerations in spinopelvic parameters and acetabular component orientation in patients with lumbar spinal fusion following total hip arthroplasty: A retrospective study

Abstract: Background: Although several authors have tried to describe the ideal acetabular component position, the influence of the spine on the orientation of the pelvis is not always considered. The aim of this study was to describe the spinopelvic behavior through body postural changes and its influence on acetabular component orientation in patients with previous spinal lumbar fusion who underwent total hip arthroplasty (THA). Methods: This is a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Five studies [ 13 15 , 18 , 19 ] reported their outcomes by distinguishing spinal fusion procedures based on the number of vertebral levels involved in the arthrodesis. As for the surgical techniques utilized in THA, considerable heterogeneity was observed, except for two studies [ 20 , 21 ] that exclusively included patients treated with the posterolateral approach. For detailed information on surgical approaches and complications specific to each study, refer to Tables 2 , 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Five studies [ 13 15 , 18 , 19 ] reported their outcomes by distinguishing spinal fusion procedures based on the number of vertebral levels involved in the arthrodesis. As for the surgical techniques utilized in THA, considerable heterogeneity was observed, except for two studies [ 20 , 21 ] that exclusively included patients treated with the posterolateral approach. For detailed information on surgical approaches and complications specific to each study, refer to Tables 2 , 3 .…”
Section: Resultsmentioning
confidence: 99%